(untitled) (Gaceta Técnica, 2019)
This paper presents the analysis of ten structural models of steel structure buildings, using different lateral concentric arches, with software Etabs-16 and Sap2000. to make an observation of the results obtained from the linear and non-linear analysis (Pushover) of the models; taking into consideration the compliance with the minimum parameters established in the Ecuadorian Construction Standard NEC-15, regarding the evaluation of the basal shear and controls so that the structures are considered seismic resistant. The definitive designs of the steel structures are obtained considering the American Institute of Steel Construction norm, and based on the summaries of materials in which indexes are detailed between the total weight and the area of the structures, reference budgets were elaborated. As a consequence, an economic evaluation was carried out to determine which type of concentric bracing turns out to be the most beneficial in terms of costs. The results obtained indicate that the most economical concentric bracing alternative corresponds to the use of reinforced concrete cutting walls, in which savings can be obtained ranging from 14,18% to 17,34% with the use of the other bracing alternatives